Effect of Long-Term Treatment with Fimasartan on Transient Focal Ischemia in Rat Brain. (13th September 2015) - Kim, Chi Kyung; Yang, Xiu-Li; Kim, Young-Ju; Choi, In-Young; Jeong, Han-Gil; Park, Hong-Kyun; Kim, Dohoung; Kim, Tae Jung; Jang, Hyunduk; Ko, Sang-Bae; Yoon, Byung-Woo
Abstract : Fimasartan is a newly developed angiotensin receptor blocker, which may have protective effects during myocardial infarction or atherosclerosis. In this context, we investigated the effects of long-term treatment with low-dose fimasartan on focal ischemia in rat brain. We induced focal ischemia in brain by transient intraluminal occlusion of middle cerebral artery (MCA) and administered low-dose (0.5 mg/kg) or regular doses (1 or 3 mg/kg) of fimasartan via intravenous routes. After the administration of low-dose (0.5 mg/kg) fimasartan, blood pressure did not decrease compared to the phosphate-buffered saline- (PBS-) control with MCA occlusion (MCAO) group. The infarct volume and ischemic cell death were reduced in the low-dose fimasartan-treated group (46 ± 41 mm 3 for 0.5 mg/kg and 153 ± 47 mm 3 for PBS-control with MCAO; P < 0.01 ) but not in the regular-dose groups. Low-dose fimasartan treatment improved functional recovery after ischemia and significantly decreased mortality. In our study, fimasartan reduced the degradation of I κ B and the formation of an inflammatory end-product, COX-2. As a result, the recruitment of inflammatory cells in the peri-infarct area decreased in fimasartan-treated group. We have demonstrated that long-term, low-dose fimasartan treatment improved outcomes after focal ischemia in the brain via a reduction of inflammation.